(-1)x(-3)=

Simple and best practice solution for (-1)x(-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-1)x(-3)= equation:


Simplifying
(-1) * x(-3) = 0

Reorder the terms for easier multiplication:
-1 * -3x = 0

Multiply -1 * -3
3x = 0

Solving
3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '3'.
x = 0

Simplifying
x = 0

See similar equations:

| 4a+2s=588 | | -6-5x=-26 | | 15z-12z-2z=15 | | 3(6e-4)=e+4 | | 7(x+2)-5=7x+9 | | 4(10x-8)=x+9 | | 18y+y-14y-2y+2y=15 | | 5x+7x+14=31 | | X+9=-x+11 | | x=4y+10 | | 0+0.99X=10+0.89X | | (x-6)(x+11)=0 | | 460+x=x | | 10(9k-1)=k+9 | | -8j+4j=12 | | (x+5)(x+5)(3x-5)=0 | | 4x^2-32x-8=0 | | 4x-15+15x+5=180 | | 2y+8=22y | | 14n-2n+n-12n=11 | | 24-7m=10 | | (-5)x(5)= | | y=-3(6)+5 | | 9x-10+2x-3=42 | | 3/5k+5=17 | | 2q+10=6 | | -11(2m-6)=3m+9(3m-10) | | 10h=s | | 3h+c+2h+3c= | | 7=-6m+5 | | -6-2(9x-2)=-5 | | 2x=x+43 |

Equations solver categories